Yield Response of Peanut (Arachis hypogaea L.) to Compound Fertilizer - Siti Maryam Harahap; Khadijah El Ramija; Erythrina Erythrina (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2020)
Harahap SM, Ramija KE, Erythrina E. 2020. Yield response of peanut (Arachis hypogaea L.)  to compound fertilize. Jurnal Lahan Suboptimal: Journal of Suboptimal Lands 9(1): 41-49.The purpose of this study was to evaluate the application effects of three different compound fertilizers on yield, and assess the income increase at different rates of compound fertilizers. Three compound fertilizers namely NPK 14-0-46, NPK 19-9-19 and NPK 11-11-11 was conducted at three different farmers’ field in Langkat District, North Sumatra Province under upland conditions. In each farmers’ field, a Randomized Complete Block Design was applied with four replications per treatment.  Seven treatments tested consisted of full rate of farmer fertilizer practice and six rates of each compound fertilizer plus half rate of farmer fertilizer practice. In each of compound fertilizer tested, pod yield and seed yield increased quadratically as increasing compound fertilizer rates. The highest pod yield and seed yield of peanut were 1649 kg/ha and 1072 kg/ha, respectively with half rate of FFP + 200 kg of NPK 14-0-46. For compound fertilizer NPK 19-9-19 the highest pod yield and seed yield were 1632 kg/ha and 1032 kg/ha with half rate of FFP + 500 kg of NPK 19-9-19 while for compound fertilizer NPK 11-11-11 the highest pod yield seed yield were 1421 kg/ha and 930 kg/ha with half rate of FFP + 250 kg of NPK 11-11-11. However, adding each  half rate of farmer fertilizer practices with  200 kg of NPK 14-0-46 or 300 kg of NPK 19-9-19 or 250 kg of NPK 11-11-11 with HypoMa-1 cultivar gave the highest values of the benefit for the farmers under upland soil in Langkat, North Sumatra.